The Effect of Tannins on Mediterranean Ruminant Ingestive Behavior: The Role of the Oral Cavity - Elsa Lamy; Ana Varela Coelho; Elvira Sales-Baptista; Célia Antunes; Ana Rodrigues Costa; Florian J. Schweigert; Ana Ferreira; André Martinho Almeida; Harshadrai Rawel; Fernando Capela e Silva (Molecules, 2011)
Sheep, cattle and goat are domestic ruminants of significant economic interest in the Mediterranean region. Although sharing the same pasture ranges, they ingest different plants and plant parts and, consequently different levels of tannins. This suggests an ability to detect and adapt ingestion according to animal physiological limits of tolerance for plant secondary metabolites. This review will detail the effects of dietary tannins on feeding behavior, and the role of the oral cavity in this process, with focus on such ruminant species. The role of salivary protein profile in tannin perception in the oral cavity, and as a defense mechanism, will be discussed.